Judicialização da saúde pública, justiça ou injustiça? - Bonfim, Dejair Pereira (2019)
The judicialization of public health is the result of the State's omission in relation to this right and, in addition to the difficulty of access to health services, has become a major obstacle to ensure access to the Unified Health System (SUS). This work aimed to perform a superficial analysis on the intensification of claims related to the right to health in the Federal District. Therefore, it was found that judicialization has been a daily strategy adopted by the population of the Federal District to guarantee their rights when violated. It turns out that judicialization is an old case to be configured as na alternative for solving health problems in the Federal District. The right to health, protected by the political charter, generates forces for today's demands.